The use of the fun activities in the english learning process of the students of the fifth years of basic education in the public schools “José Ingenieros Nº2”, “Rosa Josefina Burneo” and “Tnte. Hugo Ortiz Nº2” at Valle parish in Loja city, during the period 2008-2009 - Leon Pucha, Paulina Elizabeth (2010)
Our research work is focused on how the application of fun activities influences the learning of the English language of the students of the fifth years of Basic Education in the public schools: "José Ingenieros Nª2", "Rosa Josefina Burneo" and "Tnte. Hugo Ortiz Nº2", at Valle parish in Loja city So this problem is important because the Fun Activities allow the best and more practical understanding especially for children. We established as General Objective to analyze the influence of Fun Activities in the English Language Learning of the students. Moreover in our general hypothesis we tried to know if the application of fun activities influences in the English Language Learning of the students. In the methodology we used are: the scientific, the descriptive, the analytic – synthetic and the explicative methods, and direct observation and the surveys like techniques, also we did not apply formula since we worked with all the population. Finally we got some important results, like: The Traditional Teaching does not permit that the classes are dynamics and teachers used few fun activities because they have not received any work shop about them.